Quality management of reference services in Malaysian public university libraries - Kamaralzaman, S.; Kaur, K. (2009)
This study explores quality measurement of reference services in Malaysian public university libraries. Specifically it identifies the quality criteria used for reference service and how these criteria contribute to the mission of the library. An open ended questionnaire was used to gather qualitative data from ten public university libraries pertaining to quality issues in reference services. Most libraries use statistical data such as number of queries received and answered and duration in which a query is handled as quality indicators of the service. The libraries report an increase in the quality performance by libraries since the adoption of a quality management system based on the ISO 9001:2000 standard.